2017
DOI: 10.1007/s11883-017-0677-7
|View full text |Cite
|
Sign up to set email alerts
|

Internal Carotid Artery Occlusion: Pathophysiology, Diagnosis, and Management

Abstract: Recanalization rates remain suboptimal with systemic thrombolysis amongst patients with acute ICAO. Recent success of endovascular therapy for vessel occlusion in anterior circulation has expanded the horizons; however, few patients with cervical dissections and ICAO were included in these landmark trials. Acute ICAO responds poorly to intravenous thrombolysis and portends worse clinical outcomes. Extracranial and intracranial ICAOs have varied clinical course and imaging patterns, with discrete cervical ICAO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 79 publications
0
50
0
1
Order By: Relevance
“…If the CTO of the ICA is derived from atherosclerosis associated with calcification in the initial segment of the ICA, then severe atherosclerosis and calcification in the occluded segment may hinder the placement of the guidewire ( 113 ). Our experience is that for CTO of the ICA with recanalization, CTA or ultrasound inspection is often performed to judge whether severe atherosclerosis is present in the occlusion of the initial segment of the carotid artery.…”
Section: Factors Affecting Recanalizationmentioning
confidence: 99%
“…If the CTO of the ICA is derived from atherosclerosis associated with calcification in the initial segment of the ICA, then severe atherosclerosis and calcification in the occluded segment may hinder the placement of the guidewire ( 113 ). Our experience is that for CTO of the ICA with recanalization, CTA or ultrasound inspection is often performed to judge whether severe atherosclerosis is present in the occlusion of the initial segment of the carotid artery.…”
Section: Factors Affecting Recanalizationmentioning
confidence: 99%
“…Etiological factors for bilateral internal carotid artery occlusion include embolism, atherothrombosis, arterial dissection, vasospasm, and angitis. 2,11) In the presence of MRI-DWI the day after surgery. The hyperintensity areas in the insular cortex and parietal lobe of the right hemisphere, and a small area of the left hemisphere were larger than the areas before thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered the main reason for the occurrence of an ischemic damage of brain areas during carotid dissection. 41 Moreover, several studies showed that ineffective collateral circles are present in patients with severe atherosclerosis. 42,43 The association between altered cerebral hemodynamic and cognitive dysfunction has been widely demonstrated in subjects with carotid stenosis.…”
Section: Follow-up Cognitive Assessmentmentioning
confidence: 99%